1p/19q testing has no significance in the workup of glioblastomas. Issue 6 (9th September 2013) - Clark, K. H.; Villano, J. L.; Nikiforova, M. N.; Hamilton, R. L.; Horbinski, C.
<x xml:space="preserve">Abstract</x> Aims To determine whether testing for isolated 1p or 19q losses, or as a codeletion, has any significance in the workup of glioblastomas (GBMs). Methods Upfront 1p/19q testing by fluorescence in situ hybridization (FISH) and/or polymerase chain reaction (PCR)‐based loss of heterozygosity (LOH) was done in 491 gliomas that were histologically diagnosed as GBMs. Outcomes were determined and measured against 1p/19q results. Results Twenty‐eight showed apparent 1p/19q codeletion by either FISH and/or PCR‐based LOH, but only 1/26 showed codeletion by both tests. Over 90% of tumours with apparent codeletion by either FISH or LOH also had 10q LOH and/or EGFR amplification, features inversely related to true whole‐arm 1p/19q codeletion. Furthermore, only 1/28 tumours demonstrated an R132H IDH1 mutation. Neither 1p/19q codeletion by FISH nor LOH had an impact on GBM survival. Isolated losses of 1p or 19q also had no impact on survival. Conclusions These data suggest that (i) 1p/19q testing is not useful on gliomas that are histologically GBMs; (ii) codeletion testing should be reserved only for cases with compatible morphology; and (iii) EGFR, 10q, and IDH1 testing can help act as safeguards against a false‐positive 1p/19q result.